MiR-181c regulates MCL1 and cell survival in GATA2 deficient cells. Issue 4 (16th July 2021) - Wang, Weixin; Chen, Rui; Droll, Stephenie; Barber, Emily; Saleh, Layla; Corrigan-Cummins, Meghan; Trick, Megan; Anastas, Vollter; Hawk, Nga Voong; Zhao, Zhen; Vinh, Donald C; Hsu, Amy; et al.
Abstract: GATA2 is a transcription factor critical for hematopoiesis. Germline mutations in GATA binding protein 2 ( GATA2 ) led to haploinsufficiency, severe cytopenias of multiple cell lineages, susceptibility to infections and strong propensity to develop myelodysplastic syndrome, and acute myeloid leukemia. Mechanisms of progressive cytopenias remain unclear. MicroRNA (miRNA) represents a unique mechanism of post-transcriptional gene regulation. In this study, miRNA profiles were evaluated and eight miRNAs were found to be differentially expressed (≥2-fold, P ≤ 0.05) in patient-derived cell lines ( N = 13) in comparison to controls ( N = 10). miR-9, miR-181a-2-3p, miR-181c, miR-181c-3p, miR-486-3p, and miR-582 showed increased expression, whereas miR-223 and miR-424-3p showed decreased expression. Cell death assays indicated that miR-181c potently induces cell death in lymphoid (Ly-8 and SP-53) and myeloid (HL-60) cell lines. miR-181c was predicted to target myeloid cell leukemia (MCL)1, which was confirmed by transfection assays, resulting in significantly reduced MCL1 mRNA and decreased live cell numbers. Bone marrow analysis of 34 GATA2 patients showed significantly decreased cellularity, CD34-positive cells, monocytes, dendritic cells, NK cells, B cells, and B cell precursors in comparison to healthy controls ( N = 29; P < 0.001 for each), which was accompanied by decreased levels of MCL1 ( P < 0.05). GATA2 expression led to significant repression of miR-181c expression in transfection experiments. Conversely, knockdown of GATA2 led to increased miR-181c expression. These findings indicate that miR-181c expression is increased and MCL1 levels decreased in GATA2 deficiency cells, and that GATA2 represses miR-181c transcription. Increased miR-181c may contribute to elevated cell death and cytopenia in GATA2 deficiency potentially through down-regulation of MCL1. Graphical Abstract: GATA2 deficiency leads to increased miR-181c, decreased MCL1, and enhanced cell death which may contribute to phenotypic features of cytopenia, immunodeficiency, and bone marrow failure.